SYSTEMATIC APPROACH TO BROWNFIELDS ASSESSMENT IN LITHUANIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This paper describes situation of brownfields in Lithuania. The brownfields analysis was made according to the main aspects influencing brownfields redevelopment process the most. This paper presents the existing legislation system relative to brownfields and economic possibilities; the cleaning methods and most popular technologies in Lithuania.